Holocene palaeoenvironments from the Direndall tufa (Luxembourg) reconstructed from the molluscan succession and stable isotope records. (July 2020) - Granai, Salomé; Dabkowski, Julie; Hájková, Petra; Naton, Henri-Georges; Brou, Laurent
This paper reports the results of new malacological analyses from a thick tufa sequence at Direndall (Luxembourg). The study is temporally contextualised with radiocarbon dates and an age–depth model. The malacological study focuses on species associations to reconstruct palaeoenvironmental developments. The gradual appearance of several shade-demanding species reflects the expansion of forest environments during the early Holocene. After c. 7.5 cal. kyr BP, three phases of maximal expansion of shade-demanding species are interspersed with two phases of decline of these taxa dated between c. 7.1 and 6.5 cal. kyr BP and between c. 3.5 and 2.4 cal. kyr BP. Malacological data are discussed with previously published calcite stable isotope data from the same sequence. Strong correlations between malacological data and δ 13 C profile are highlighted over the whole sequence. Combined influences of local environmental conditions and regional climatic trends are emphasised. The sequence provides a palaeoenvironmental succession free of any anthropic influence.